Unexpected additive effects of minocycline and hydroxychloroquine in models of multiple sclerosis: Prospective combination treatment for progressive disease?. (October 2018) - Faissner, Simon; Mahjoub, Yasamin; Mishra, Manoj; Haupeltshofer, Steffen; Hahn, Jennifer Nancy; Gold, Ralf; Koch, Marcus; Metz, Luanne M; Ben-Hur, Tamir; Yong, V Wee
Background: Most multiple sclerosis (MS) patients succumb to a progressive phenotype. Continued lymphocyte activity in the brain, microglia-mediated injury, iron deposition, and oxidative stress are characteristics of progressive MS. Objective: As minocycline and hydroxychloroquine have been shown to inhibit microglia, we evaluated their effects on other outcomes relevant for progression. Methods: Medications were evaluated in culture and in mice with acute and chronic experimental autoimmune encephalomyelitis (EAE). Results: Both medications individually reduced iron neurotoxicity and a combination effect was not observed. Hydroxyl radical scavenging activity was manifested by minocycline only. Minocycline reduced T-cell proliferation more prominently than hydroxychloroquine; an aggregate effect occurred at low but not high concentrations. B-cell proliferation was mitigated to a greater extent by hydroxychloroquine and an additive effect was not evident. In EAE, suboptimal doses of minocycline and hydroxychloroquine individually delayed onset of clinical signs, while their combination suppressed clinical manifestations until treatment was stopped. In Biozzi ABH mice, a model of progressive MS, the chronic phase was beneficially altered using the combination. Conclusion: While minocycline and hydroxychloroquine did not manifest additive effects in most culture assays, their combination at suboptimal doses in EAE unexpectedly exceeded their individual activity. Minocycline and hydroxychloroquine combined are candidate treatments for progressive MS.